Pemberdayaan Pokdakan Suka Maju Melalui Pemanfaatan Limbah Industri Dan Pengaman Kolam Dengan IOT - Herijanto, Soegeng; Watiningsih, Tri; Wasito, Wasito; Grasela Mawardani, Nur; Rian Maulana, Okta (PELITA NUSA TENGGARA, 2025)
This Community Service Program (PKM) aims to empower the Suka Maju Fish Farming Group in Langgongsari Village, Banyumas Regency, through the utilization of industrial waste as an alternative feed ingredient and the application of Internet of Things (IoT) technology for pond security systems. The partners consist of 30 members from a combination of three Pokdakan: Ulam Sari, Mina Mandala, and Mugi Barokah. The implementation method uses a mentoring and training approach including institutional strengthening, cultivation management training, industrial waste-based feed formulation, and the installation of IoT devices as a pond monitoring system. The results of the activities show an increase in the understanding and skills of partner members in tilapia cultivation techniques, the provision of seed through the mina padi system, and the ability to utilize industrial waste as an alternative feed. IoT technology also improves the security of the cultivation ponds. This program contributes to institutional strengthening, increased production capacity, and the cessation of freshwater fish farming businesses.